Kinetics and Mechanistic Aspects of Oxidation of Acetophenones by N-Bromophthalimide in Presence of Mercuric Acetate - Anjum, Amena; Srinivas, P. (Asian Journal of Chemistry, 2016)
The reactions of N-bromophthalimide (NBP) with acetophenones (ACP) have been studied in presence of excess of mercuric acetate in aqueous acetic acid medium. NBP acts as moderate oxidant with a redox potential of 1.09 V. The reaction kinetics were first order in [NBP] and fractional order in [acetophenone]. Variation of phthalimide, mercuric acetate and ionic strength had an insignificant effect on reaction rate. The solvent effect revealed a positive dielectric effect. The stoichiometric ratio of ACP : NBP was 1 : 2 and the products of oxidation were benzoic acid and formaldehyde. Hammetst plot of log k vs. s+ gave r+ = -0.52 and Exner’s plot gave isokinetic temperature b = 263 K. Thermodynamic and activation parameters have been evaluated and a mechanism consistent with the kinetic data has been proposed.